Isolation of Phenolic Acids from Land Kale (Ipomoea reptans Poir) and Antioxidant Activity - Enny Fachriyah; Sofiana Nur Aziiza; Ismiyarto Ismiyarto; Purbowatiningrum Ria Sarjono; Dwi Hudiyanti; Sumariyah Sumariyah (Jurnal Kimia Sains dan Aplikasi, 2024)
Land kale or Ipomoea reptans Poir is widely consumed by Indonesian people. Land kale plants can be used as natural antioxidants because they contain polyphenolic compounds, one of which is phenolic acid. This research was carried out to determine the antioxidant activity and isolate phenolic acid compounds contained in land kale plants (Ipomoea reptans Poir). The sample used was an ethanol extract of land kale. The total phenolics were determined using the Folin-Ciocalteu method. Phenolic acids were isolated using alkaline hydrolysis and acid hydrolysis and without hydrolysis methods. Separation of isolates was carried out using the TLC method. The structure was identified using UV-Vis spectrophotometry and LC-MS/MS. Antioxidant activity was measured using the DPPH method. The total phenolics of land kale ethanol extract were 71.2420 ± 0.0791 mg/g GAE. TLC showed that the HB, HA, and TH fractions contained caffeic acid and ferulic acid compounds. Separation of the (HB) fraction produced three isolates: B2 with a yellow color, B3 with a slightly yellowish color, and B4 which is colorless. Isolate B2 was identified as potentially containing caffeic acid, while isolate B3 was indicated to potentially contain ferulic acid through analysis using a UV-Vis spectrophotometer. Isolate B4 was thought to have a hydroxybenzoic acid framework after being determined using LC-MS/MS. The ethanol extract of land kale has strong antioxidant activity because it produces an IC50 value of 94.83 mg/L.